4CPS-209 An exploration into a pharmacist-led medicines reconciliation service in an acute hospital setting. (24th March 2020) - Shine, C; Kieran, M; Meegan, C
Abstract : Background and importance: Accurate medication records are essential in preventing errors, avoiding harm, aiding diagnosis and treatment planning. Prescribing errors are more prevalent on hospital admission 1 2 Medicines reconciliation (MR), 'the formal process in which healthcare professionals partner with patients to ensure accurate and complete medication information transfer at interfaces of care', ensures accurate medication record generation. 3 MR is undertaken to varying degrees in many institutions, by a variety of healthcare professionals, each with their own focus, priorities and methods. 4 MR is a WHO patient safety priority outlined in the High 5s Project. 3 Aim and objectives: To determine views and opinions of doctors towards a pharmacist-led MR service in an acute hospital and to ascertain what doctors identify as MR barriers and facilitators. Material and methods: A self-completion questionnaire using mixed methodology was conducted. This involved analysing data both qualitatively and quantitatively. Data were collected simultaneously. Inclusion criteria: all doctors working at the Mater Misericordiae University Hospital (MMUH). Exclusion criteria: none. Data were analysed on site using a password protected spreadsheet on Microsoft Excel. Detailed content and thematic analysis were performed to identify common concepts. A 10% proportion of the data was checked by an independent reviewer Results: The positive impact on patient care and safety demonstrated by MR was acknowledged by 98% (n=50): 94% (n=49) agreed MR saved them time while 92% (n=48) recognised MR decreased their workload, 90% (n=46) of participants were satisfied with the MMUH MR service and 94% (n=49) agreed MR was accurate. Participants called for dedication of pharmacy resources to MR (88%, n=46), and service expansion to include all patients on admission, care transition and discharge was advocated by participants (79%, n=41; 86%, n=44; and 79%, n=41, respectively). The most important facilitator was verbal communication of MR discrepancies. The most important barrier was current service limitations. Thematic analysis identified four themes: patient safety (n=33), workload implications (n=9), MR usefulness (n=52) and service development (n=56). Conclusion and relevance: Prescribers viewed the pharmacist-led MR service as a positive useful initiative, saving prescribers time, and increasing patient care and safety hospital wide. References and/or acknowledgements: 1. Porcelli PJ, Waitman LR, Brown SH. A review of medication reconciliation issues and experiences with clinical staff and information systems. Appl Clin Informatics 2010;1:442–461. 2. FitzGerald RJ. Medication errors: the importance of an accurate drug history. Br J Clin Pharmacol 2009;67:671–675. 3. World Health Organization. Standard operating protocol assuring medication accuracy at transitions in care, 2014. 4. Barnsteiner JH. Medication reconciliation. In: Hughes RG, editor. Patient safety and quality an evidence-based handbook for nurses 2008;38:2–459. No conflict of interest.